Innovative Model of Socio-Professional Development of a Student’s Personality - E. F. Zeer; V. S. Tretyakova; M. V. Zinnatova (Образование и наука)
Introduction. The expansion of infocommunication and digital technologies, the uncertainty of professional future and accelerated changes in the social and professional future of a modern man and the radical transformation of socio-professional environment require qualitative changes in the Russian education, revision of its methodology, content and technologies of training for the postindustrial economy. Today, “work in the specialty” is increasingly losing its importance, hard professional knowledge and hard skills are not decisive in the professional development and building of a successful career. Flexible, soft skills are becoming increasingly required. Soft skills allow a person to be successful regardless of the specifics of the activity and the direction in which he or she works. However, educational programmes, developed on the basis of Federal State Standards, continue to be currently directed by “mass production” and “conveyor production”, which is contrary to objective requirements of the labour market and students’ requirements.The aim of the present research is the development and theoretical-methodological justification of an innovative educational model of socio-professional development of a student personality. The introduction of this model into the practice of universities and secondary vocational educational institutions will allow the graduates to realise their potential in new realities through the formed transprofessional qualities and extraprofessional competencies.Methodology and research methods. Methodological framework of the research is based on the concept of subject-activity approach, according to which the personality is considered as an active, self-improving, self-actualising and self-determining actor; process and project approaches; as well as the methodology of convergence, which provides a synergistic effect of interaction of socio-humanitarian, natural-scientific and industrial-technical disciplines. The authors used the methods of various types of analysis including SWOT analysis; logical-semantic and structural-functional modelling.Results. The authors actualised the problem of creating an innovative educational content, which expands the range of professional knowledge and skills required of competitive personnel, who are capable and ready to preadapt to the rapidly changing socio-professional conditions. The educational model proposed by the authors is built on a modular principle. The targets, the content of modules, elective disciplines representing this or that module are defined. The content of each module is focused on the final result of educational activity: professional, diagnostic, competence, technological, functional. The mechanism of the model implementation is to build an individual student professional perspective aimed at practical action in order to improve the level of qualification, ability to work, enrichment of professional and personal qualities and behavioural patterns.Scientific novelty of the present research consists in the formation of interdisciplinary scientific knowledge (at the intersection of psychology, pedagogy, philosophy, occupational studies) on the methodology of the modelling, organisation and content of professional education taking into account modern challenges and demands of the digital economy. When training pedagogical personnel, it is necessary to create professional transcendence – an ability to go beyond particular professional activities, to find new meanings in it and beyond it and to solve nonstandard tasks.Practical significance. The presented innovative model of socio-professional development can be focused on the training of specialists at different levels of education, including additional education. The research materials can be useful to developers of educational programmes and training technologies of vocational education, to managers and specialists of educational organisations when making management decisions and organising the educational process.